2012
DOI: 10.1016/j.jash.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody activation of beta-adrenergic and muscarinic receptors contributes to an “autoimmune” orthostatic hypotension

Abstract: Background Orthostatic hypotension (OH) is characterized by an abnormal autonomic response to upright posture. Activating autoantibodies to β1/2-adrenergic (AAβ1/2AR) and M2/3 muscarinic receptors (AAM2/3R) produce vasodilative changes in the vasculature that may contribute to OH. Methods and Results IgG from 6 patients with idiopathic OH harboring autoantibodies and from 10 healthy control subjects were examined for: 1) β1AR and M2R activity with a perfused Purkinje fiber assay and PKA assay in H9c2 cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 15 publications
4
32
0
1
Order By: Relevance
“…More importantly, C5F2 perfusion of resistance arterioles produced a potent vasodilatation, which could also be inhibited by the ␤ 2 AR blocker and ␤ 2 AR ECL2 peptide, indicating that antibody activation of vascular ␤ 2 AR may contribute to systemic vasodilatation. The functional activity of C5F2 was consistent with that of serum IgG polyclonal autoantibodies from the patient and of serum anti-␤ 2 AR autoantibodies harbored in a subgroup of postural hypotension patients (21,22). ␤ 2 AR-mediated vasodilatation in resistance arteries involves two different mechanisms: direct vasodilatation via activation of cAMP/PKA-mediated dephosphorylation of the smooth muscle myosin (37) and endothelial nitric oxidemediated vasodilatation (38).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…More importantly, C5F2 perfusion of resistance arterioles produced a potent vasodilatation, which could also be inhibited by the ␤ 2 AR blocker and ␤ 2 AR ECL2 peptide, indicating that antibody activation of vascular ␤ 2 AR may contribute to systemic vasodilatation. The functional activity of C5F2 was consistent with that of serum IgG polyclonal autoantibodies from the patient and of serum anti-␤ 2 AR autoantibodies harbored in a subgroup of postural hypotension patients (21,22). ␤ 2 AR-mediated vasodilatation in resistance arteries involves two different mechanisms: direct vasodilatation via activation of cAMP/PKA-mediated dephosphorylation of the smooth muscle myosin (37) and endothelial nitric oxidemediated vasodilatation (38).…”
Section: Discussionsupporting
confidence: 70%
“…We recently reported the association of vasodilatory polyclonal autoantibodies to the ␤ 2 -adrenergic receptor (␤ 2 AR) and/or M3 muscarinic receptor in postural hypotension patients (21,22). These autoantibodies possess sufficient bioactivity to alter the postural vascular response, thus contributing to the pathophysiology of postural hypotension, especially the "idiopathic" type, i.e.…”
mentioning
confidence: 99%
“…4, 13 We have recently reported for the first time the association of agonistic autoantibodies in 6 patients with demonstrable orthostasis. 14 This mechanistic study demonstrated significant vasodilatory activity associated with autoantibodies directed toward the β2-adrenergic receptor (β2AR) and M3 muscarinic receptor (M3R). Although the IgG purified from these patients demonstrated marked vasodilatory activity, the combination of potentially opposing effects from other agonistic autoantibodies and their diverse presentation within the small number of patients made it difficult to develop an impression of the autoantibody frequency and physiological role in patients subject to orthostatic symptomatology.…”
Section: Introductionmentioning
confidence: 83%
“…Several features of idiopathic orthostatic hypotension have been attributed to hypoactive or hyperactive states of adrenergic receptors of the sympathetic nervous system. Recent data indicate that autoimmune lesions of the β-AR signaling pathway could be one of the contributing factors to orthostatic intolerance [47,48], but still there are no available data about the contribution of GRK to this syndrome.…”
Section: Role Of G Protein Related Kinases In Sympathetic Neurocirculmentioning
confidence: 99%